Selective Fair Behavior as a Function of Psychopathic Traits in a Subclinical Population - Osumi, Takahiro; Ohira, Hideki (Frontiers in Psychology, 2017)
Psychopathy is a group of personality traits that are associated with violations of social norms. Previous studies have suggested that people with psychopathic traits in subclinical populations do not necessarily display antisocial, self-defeating behaviors, and instead may strategically show adaptive behaviors in response to cues during reciprocal social interactions. Therefore, in the present study, we examined whether the association between psychopathic traits and unfair behavior can be moderated by a potential for punishment and social distance (anonymity), which are known to facilitate fair behavior. We focused on two psychopathic traits: primary and secondary psychopathy. Primary psychopathy is characterized by callousness, shallow affect, manipulation, and superficial charm. In contrast, secondary psychopathy is associated with impulsivity and lack of long-term goals, and is related to hostile behavior. A total of 348 undergraduate students determined the amounts of money that they would offer to strangers or friends at their university in hypothetical scenarios of the ultimatum game (UG) and the dictator game (DG). While gender affected decisions in the hypothetical scenarios of the DG, it did not interact with psychopathic traits. The score for primary psychopathy on the Levenson self-report psychopathy scale predicted unfair monetary offers to strangers in the DG, where participants could not be punished. However, compared with their offers in the DG, individuals with higher scores for primary psychopathy made larger offers in the UG, where low offers could trigger punishment from the recipient. Moreover, primary psychopathy did not decrease the amounts of offers in either game when the participant considered the recipient to be a friend. On the other hand, secondary psychopathy was not associated with differences in behavioral fairness depending on a potential for punishment or social distance. Based on these findings, we discuss strategic social skills as a function of primary psychopathy.